Reward system and its impact on employee motivation : a case study of a Malaysia service company (PUSPAKOM SDN. BHD) - Ezza Izzyana, Mohd Nor (2014)
The aim of this research is to study the reward system and its impacts on employee motivation. For reward system, it was divided into two categories. One is extrinsic reward which consists of pay, bonus, and promotion. The other one is intrinsic reward, which consists of responsibilities, meaningful work and achievement. Both of them are set as the independent variables. Then, employee motivation is the dependent variable. 132 respondents from Puspakom Sdn. Bhd. were surveyed by questionnaire. The collected data was analyzed by using descriptive statistic (frequency), reliability analysis (Cronbach’s alpha), correlation test (hypothesis testing), and regression analysis. Results show that there are signiﬁcant positive relationships between reward system dimensions (pay, bonus, promotion, responsibilities, meaningful work, and achievement) and employee motivation and the ﬁndings are in accordance with previous researches